Evaluación de parámetros ambientales y propuesta de reducción de recursos para optar por el galardón del Programa Bandera Azul Ecológica en la Sede Central de Bancrédito. - Rodríguez-Rodríguez, Alina (Instituto Tecnológico de Costa Rica, 2013)
The study is a reduction proposal in the consumption of resources in the Bancrédito head office, based on the evaluation parameters of the category of Actions to Face the Climate Change of the Bandera Azul Ecológica Program (PBAE). To achieve the objective a baseline consumption study was established for: water, paper, electricity, fuels and aerosols based on data from 2011. Fieldwork was performed to get the inventory of the lighting and air conditioners. In addition, to determining the environmental indicators of consumption according to the parameters evaluated by PBAE, the current situation was determined regarding organizational consumption practices and consulted with experts in the topics covered in the project. The baseline environmental indicators of consumption for 2011were: • 3.6 kg of paper per employee per month • 1073.3 liters of water per employee per month • 3911.9 liters of gasoline per trimester • 4072.3 liters of diesel per trimester • 141.1 kWh of electricity per month per employee To achieve the indicators goal and to obtain the award of PBAE recommendations are given for the improvement in the areas of lighting, air conditioning, electronics use, fuel, water and paper. These recommendations are expected to generate savings of 8 476 248,274 million colones. The investigation showed that in the Bank there is a high potential for reduction in consumption of resources. This increases the chances to getting the award of PBAE as long as improvements are made in such activities
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2012.
Keywords: Ecología humana; Reciclaje; Reutilizar; Energía limpia; Cambio climático